Women's questions - General Election 1924 (1924)
1924 1918-1939 "Women's questions - General Election 1924" [EP0204], 1924 This leaflet was probably produced by the Women's International League for Peace and Freedom in 1924. It encourages women to vote Labour in the October 1924 General Election. In the 1923 General Election, the Labour Party won 191 seats. Although the Conservatives had 258, Ramsay MacDonald agreed to head a minority government, and therefore became the first member of the party to become Prime Minister. MacDonald had the problem of forming a Cabinet with colleagues who had little administrative experience. The Conservative Party won 412 seats in the 1924 Election and formed the next government. With his 151 Labour MPs, MacDonald became leader of the Opposition.